Aprimoramento na qualidade nutricional da carne mecanicamente separada da tilápia do Nilo e sua aplicação em empanados - Signor, Flávia Renata Potrich (2018)
The consumption preference for the tilapia meat by Brazilians is represented by fillet, being this the main product commercialized by the industries that benefit of the specie. In industry, the fillet production cost is high because of the low fish utilization, which in turn, it generates residues that can potentially be transformed into commercially viable by-products, such as mechanically separated meat (MSM). In this sense, this work aims to improve the nutritional quality of Nile tilapia MSM (Oreochromis niloticus) through the pressing process for the elaboration of new products with added value. The present study was divided in two stages: 1st stage - Study the effect of pressing process on the nutritional quality of the Nile tilapia MSM and the effect of the addition fish-based condiment on development of the MSM patties (article 1). The results showed that the pressing process improves the nutritional quality of the tilapia MSM and the addition fish-based condiment in the patties provides a better sensorial acceptance of the product. In the 2nd stage - Evaluates the effects of the addition of pregelatinized starch and dextrin in the preparation of MSM patties obtained from fillet waste from Nile tilapia (Article 2). The results demonstrated that the addition of pregelatinized starch and dextrin improves the texture of tilapia MSM patties, as well as their sensorial characteristics. Based on the data obtained, it can be concluded that the residues (carcass) generated in the process of fillet processing can be a viable alternative as raw material for the elaboration of new structured products, adding value and enabling the fish processing industry to increase profits.